Food Authentication: Techniques, Trends and Emerging Approaches - González-Domínguez, Raúl (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Multiple factors can directly influence the chemical composition of foods and, consequently, their organoleptic, nutritional, and bioactive properties, including their geographical origin, the variety or breed, as well as the conditions of cultivation, breeding, and/or feeding, among others. Therefore, there is a great interest in the development of accurate, robust, and high-throughput analytical methods to guarantee the authenticity and traceability of foods. For these purposes, a large number of sensorial, physical, and chemical approaches can be used, which must be normally combined with advanced statistical tools. In this vein, the aim of the Special Issue "Food Authentication: Techniques, Trends, and Emerging Approaches" is to gather original research papers and review articles focused on the development and application of analytical techniques and emerging approaches in food authentication. This Special Issue comprises 12 valuable scientific contributions, including one review article and 11 original research works, dealing with the authentication of foods with great commercial value, such as olive oil, Iberian ham, and fruits, among others.